Pengaruh Promosi Terhadap Penjualan Di Trattoria Cucina Italiana Jakarta - RD Rita Ritasari; Intan Junita Sari (Politeknik Sahid, 2018)
Trattoria Cucina Italiana is one of Italian restaurant located in jakarta. Due to the number of Italian restaurants spread in various areas in Jakarta, need a good promotion in order to compete with other restaurants. The purpose of this research is to make a positive contribution to the sale at Trattoria Cucina Italiana. The sample used is 100 respondents with data processing using multiple linear analysis method. The results of this study indicate that, there are significant positive results promotion to sales at Trattoria Cucina Italiana Jakarta.The results of hypothesis testing show that is a positive and significant influence. Statistically theories relating to the effect of promotion on sales. Has been proven in this study.description of acceptance of the hypothesis in question can be explained, as follows : Statistically, it is translated that your promotion has a positive and significant effect on sales. The higher the effort to increase promotion, it will increase sales progressicely